Development Of Coconut Agroindustry Business Institutions In Konawe District, Southeast Sulawesi Province - Ulyasniati Ulyasniati; La Rianda; Tamrin Tamrin; Awaluddin Hamzah (International Forum of Researchers and Lecturers, 2023)
This research aims to analyze the institutional system of coconut agro-industry businesses in Konawe Islands Regency, Southeast Sulawesi Province. The scope of this research is the institutional processing business, namely institutional form, raw material requirements, institutional structure, capital, decision making, data collection techniques through interviews, FGD and expert questionnaires (ISM). Based on the research results, it shows that: The key elements of the palaku coconut processing business development system in Konawe Islands Regency are coconut farmers and consumers of processed coconut products. The key elements needed by players in the coconut processing business development system are easy access and guaranteed marketing of processed products, the need for rehabilitation, intensification and extensification of coconut plants. Sustainability of institutional development of coconut processing businesses requires assistance from universities (PTN-PTS) whose role is to connect between parties which have been an obstacle for farmers and coconut processors.